A System Dynamics Approach for Sustainability in the Natural Gas Energy Market - Ivgin, Mehmet; Demirel, Tufan (International Journal of Energy Economics and Policy, 2025)
The natural gas energy market is a dynamically-complex system, comprising various interconnected components and involving a diverse array of stakeholders. Achieving sustainable development within this sector necessitates a comprehensive understanding of its components and their dynamic es that focus solely on specifiinteractions. Traditional approaches to improving energy systems have often adopted narrow perspectivc components, disregarding their interconnected nature. Such approaches limit our comprehension of the system and hinder our ability to mitigate undesirable outcomes. This paper employs a System Dynamics approach to construct a comprehensive systems model of the natural gas energy market, employing a case study centered around Türkiye. The model provides a holistic visualization of the energy market, identifying crucial feedback mechanisms that shape the sector’s behavior. Furthermore, this model serves as a shared language, facilitating a better understanding of the market among stakeholders and providing a platform to identify key leverage points for implementing systematic intervention strategies, thereby advancing the development of a sustainable natural gas energy market. Research findings reveal significant risks associated with policy decisions concerning energy security and environmental interventions, particularly in relation to the oil and gas components and CO2 emissions.